Mesh removal and reconstruction with posterior components separation technique for delayed mesh infection developed 10 years after abdominal incisional hernia repair: a rare case report - Tetsuro Tamura; Yoshihiro Ohata; Fujio Katsumoto (Surgical Case Reports)
Abstract Background Very few literatures can be found reporting cases and treatment strategies of late-onset mesh infection after abdominal incisional hernia reconstruction. Here, we report a rare case of delayed mesh infection developed 10 years after abdominal incisional hernia repair, which was successfully treated by mesh removal and reconstruction with posterior components separation technique. Case presentation A 66-year-old man, who underwent reconstruction of abdominal incisional hernia by retroperitoneal Composix mesh application 10 years prior, developed 12 × 6.0 × 2.5 cm subcutaneous abscess followed by methicillin-resistant Staphylococcus aureus (MRSA)-related mesh infection. The operation was performed excising the abscess wall without damaging peritoneum, and huge intermuscular defect was successfully reconstructed by posterior components separation technique application. Conclusions An early decision of excising contaminated mesh would be preferable to extensive conservative treatments when mesh infection is suspected. Components separation technique application can be of great help when designing reconstruction of huge intramuscular defect after removal of infected mesh.